2007
DOI: 10.15369/sujms1989.19.189
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Gene Maspin Induces Apoptosis in Stomach and Colon Cancer

Abstract: : The tumor suppressor gene maspin serves to inhibit cancer infiltration/metastasis, and maspin's involvement in apoptosis-inducing action has been noted. In the current research, we studied the relationship between maspin expression and apoptosis using clinical specimens of stomach and colon cancer. Subjects were 39 cases of stomach cancer (20 cases of early cancer, 19 cases of advanced cancer) and 36 cases of colon cancer (16 cases of early cancer, 20 cases of advanced cancer) in which the cancer was surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Nevertheless, the clinicopathological features of each This is the rst paper to investigate and discuss the expression of maspin in colorectal serrated polyps. In previous studies we have demonstrated maspin expression at a high rate in several metaplastic, dysplastic, and precancerous lesions, such as esophageal dysplasia, gastric intestinal metaplasia and adenoma, pancreatic intraepithelial neoplasia, intraductal papillary-mucinous adenoma, and colorectal adenoma [11][12][13][14][15][16] . Zheng et al 18 and Boltze 19 have also reported a high rate of maspin expression in specimens of colorectal adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the clinicopathological features of each This is the rst paper to investigate and discuss the expression of maspin in colorectal serrated polyps. In previous studies we have demonstrated maspin expression at a high rate in several metaplastic, dysplastic, and precancerous lesions, such as esophageal dysplasia, gastric intestinal metaplasia and adenoma, pancreatic intraepithelial neoplasia, intraductal papillary-mucinous adenoma, and colorectal adenoma [11][12][13][14][15][16] . Zheng et al 18 and Boltze 19 have also reported a high rate of maspin expression in specimens of colorectal adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that downregulation of maspin expression correlates with progression and metastatic status in several cancers 10 11 . We have also studied the expression pattern of maspin in the esophagus, stomach, colorectum, pancreas, and lung [11][12][13][14][15][16][17] , where a high rate of maspin expression is commonly observed during cancer formation from precancerous lesions, and maspin expression tends to be suppressed when invasion and metastasis of cancer cells occurs. Similar results in the colorectum have been previously reported by several authors 18 19 .…”
Section: Introductionmentioning
confidence: 99%